The Influence of Competency, Compensation, and Implementation of Standard Operational Procedures on Employee Work Productivity PT. Riau Media Television - Dwianjani, Prisha Olivia; Mardhiyah, Ainun (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2024)
Employees must work optimally and efficiently so that the company can have a high productive level. The achievement of company targets will certainly affect the rewards that employees receive by following the SOPs that have been prepared by the company. This has good intentions because it is directly proportional to the maximum compensation that employees will get as the best human resources. This study aims to analyze how the influence of competence, compensation and the application of standard operating procedures on the work productivity of employees at PT. Riau Media Television. This study uses a quantitative research method with a causal associative approach. The population in this study are employees of PT. Riau Media Television, with a sample of 36 respondents. The results showed that the variables of competency, compensation and implementation of standard operating procedures had a simultaneous effect on employee work productivity with a level of influence of 67.2%, while the remaining 32.8% was influenced by other variables not discussed in this study.